A Chimeric Humanized Mouse Model by Engrafting the Human Induced Pluripotent Stem Cell-Derived Hepatocyte-Like Cell for the Chronic Hepatitis B Virus Infection - Yuan, Lunzhi; Liu, Xuan; Zhang, Liang; Li, Xiaoling; Zhang, Yali; Wu, Kun; Chen, Yao; Cao, Jiali; Hou, Wangheng; Zhang, Jun; Zhu, Hua; Yuan, Quan; et al. (Frontiers in Microbiology, 2018)
Humanized mouse model generated by grafting primary human hepatocytes (PHHs) to immunodeficient mouse has contributed invaluably to understanding the pathogenesis of hepatitis B virus (HBV). However, the source of PHHs is limited, which necessitates the search for alternatives. Recently, hepatocyte-like cells (HLCs) generated from human induced pluripotent stem cells (hiPSCs) have been used for in vitro HBV infection. Herein, we developed a robust human liver chimeric animal model to study in vivo HBV infection by engrafting the hiPSC-HLCs to Fah-/-Rag2-/-IL-2Rγc-/- SCID (FRGS) mice. After being optimized by a small molecule, XMU-MP-1, the hiPSC-HLCs engrafted FRGS (hHLC-FRGS) mice displayed approximately 40% liver chimerism at week six after engraftment and maintained at this level for at least 14 weeks. Viremia and HBV infection markers include antigens, RNA, DNA and covalently closed circular DNA (cccDNA) were detectable in HBV infected hHLC-FRGS mice. Furthermore, hiPSC-HLCs and hHLC-FRGS mice were successfully used to evaluate different antivirals. Therefore, we established a humanized mouse model for not only investigating HBV pathogenesis but also testing the effects of the anti-HBV drugs.